2014
DOI: 10.1111/1471-0528.12599
|View full text |Cite
|
Sign up to set email alerts
|

Fear of childbirth in nulliparous and multiparous women: a population‐based analysis of all singleton births in Finland in 1997–2010

Abstract: Objective To identify risk factors for fear of childbirth (FOC) according to parity and socioeconomic status, and to evaluate associations between FOC and adverse perinatal outcomes.Design A cohort study.Setting The Finnish Medical Birth Register.Population All 788 317 singleton births during 1997-2010 in Finland.Methods Fear of childbirth was defined according to the International Classification of Diseases code O99.80, and its associations with several risk factors and perinatal outcomes were analysed by mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
193
7
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(221 citation statements)
references
References 34 publications
(77 reference statements)
19
193
7
2
Order By: Relevance
“…Our results support the findings that severe FOC is associated with a previous CS and instrumental delivery in parous women (Ryding et al 1998;Rouhe et al 2009;Nilsson et al 2012;Lucasse, Schei, Ryding 2014;Söderqvist, Wijma & Wijma 2002), and with elevated maternal age in nulliparous women (Räisänen et al 2014). We did not find any correlation between gestational age, social support (measured as marital status in our study) or educational level, as has been suggested by others (Saisto et al 2001;Laursen, Hedegaard & Johansen 2008;Lucasse, Schei, Ryding 2014).…”
Section: Generalsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results support the findings that severe FOC is associated with a previous CS and instrumental delivery in parous women (Ryding et al 1998;Rouhe et al 2009;Nilsson et al 2012;Lucasse, Schei, Ryding 2014;Söderqvist, Wijma & Wijma 2002), and with elevated maternal age in nulliparous women (Räisänen et al 2014). We did not find any correlation between gestational age, social support (measured as marital status in our study) or educational level, as has been suggested by others (Saisto et al 2001;Laursen, Hedegaard & Johansen 2008;Lucasse, Schei, Ryding 2014).…”
Section: Generalsupporting
confidence: 89%
“…In mixed samples of nulliparous and parous women, severe FOC is found to be associated with prolonged labour (Sydsjö et al 2014, Johnson & Slade 2003, more use of instrumental deliveries (Ryding 1993;Sjögren & Thomassen 1997), and more pain relief (Sjögren & Thomassen 1997;Alehagen, Wijma & Wijma 2006) and CS (Ryding et al 1998;Gottvall & Waldenström 2002;Sydsjö et al 2013;Räisänen et al 2014;Ryding et al 2015). In similar samples the aforementioned vicious circle has been reported: the phenomenon of finding women who report high FOC before, during and after delivery (Zar, Wijma & Wijma 2001;Alehagen, Wijma & Wijma 2006;Sluijs et al 2012), which thus augments the woman's risk for experiencing the delivery as traumatic.…”
Section: Consequences Of Severe Focmentioning
confidence: 86%
“…Depression, anxiety and stress scores were positively but weakly associated with fear scores across samples, a relationship that has also been demonstrated among pregnant women (2,6,(44)(45)(46). The short version of the Depression-Anxiety Stress Scale was a reliable measure across student samples, adding to a growing body of evidence that supports use of the scale in non-clinical samples (41,42).…”
Section: Discussionmentioning
confidence: 65%
“…Severe fear of childbirth affects 2.5% of nulliparas and 4.5% of multiparas (6) and is characterized by nightmares, physical complaints, and difficulties concentrating on work or family activities. Common childbirth fears include worries about the health and safety of the baby, and fear of intolerable pain, prolonged labour, an inability to cope with labour and unsupportive hospital staff (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation